Re-Examining the Operating Performance of China’s Listed Companies with Unexpected Earnings Disclosure - Chou, Pai-Lung; Chi, Tsung-Li; Lin, Jia-Jun (Indian Journal of Finance, 2008)
The unexpected earnings disclosure could be important indicator for investors while making their decisions and investors will get closely to understand China’s target companies’ operating performance. China’s disorder stock market could be solid into the asymmetry information between holding shareholders and small investors, and entrepreneurship disappears when operating dilemma comes up progressively. Most of operators tend to delay the announcement of bad news about earning reports, and consequently overslip the timeliness of annual earnings disclosure. Therefore, this study applied the panel data regression with fixed effect to analyze the impact of net income on five forces of financial indices (Profitability; Productivity; Activity; Growth; Stability) with earnings disclosure. The result showed that unexpected earnings news could provide more significance than traditional financial indices.